Ґрунтова мікобіота та фітоедафон крейдяних відслонень долини р. Вовча (Харківська обл.) - Віннікова, О.І. (Український ботанічний журнал, 2011)
Изучены микобиота и фитоэдафон меловых обнажений, расположенных на северо-востоке Харьковской обл. Показано, что микобиоте и фитоэдафону исследованной территории присущи черты мико- и альгофлоры лесных биогеоценозов. Особенностями микобиоты и фитоэдафона данных кальцифицированных почв можно считать значительную долю родов Aspergillus и Fusarium, а также водорослей из отдела Cyanophyta, при невысокой степени распространенности большинства представителей указанных таксонов на исследованных стационарах. Mycobiota and phytoedaphon of the cretaceous chalk outcrops located in the northeast of Kharkiv Region, Ukraine, were studied. Generally, mycobiota and phytoedaphon of the studied area are shown to have the traits of myco- and algoflora of forest biocoenoses. The specific features of the mycobiota and algoflora of calcificated soils are significant shares of Aspergillus and Fusarium genera and Cyanophyta algae to the overall species diversity. However, majority of species of these taxa showed a scarce distribution on the studied plots.